Crystal structure of (E)-N-(2-(benzylamino)-2-oxo-1-(4-oxo-4H-chromen-3-yl)ethyl)-N-(4-bromophenyl)-3-chloroacrylamide hydrate, C27H22BrClN2O5 - Meng Jiang Ping (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C27H22BrClN2O5, triclinic, P1̄, a = 6.8549(4) Å, b = 13.2863(12) Å, c = 14.3690(13) Å, α = 85.944(7)°, β = 84.882(6)°, γ = 89.932(6)°, V = 1300.18(18) Å3, Z = 2, Rgt(F) = 0.0655, wRref(F2) = 0.1841, T = 293(2) K.